Unmasking the Hidden: A Rare Case of Miliary Lung Adenocarcinoma With Pneumothorax Mimicking Tuberculosis - Sajan Sah; Sudeep Acharya; Rabindra Dhakal; Sakura Thapa; Mahreen Anwar; Shamsuddin Anwar; Halim El-Hage; Dany Elsayegh (Annals of Internal Medicine: Clinical Cases)
This report details a rare case of a man with advanced primary lung adenocarcinoma who presented with miliary metastasis and pneumothorax that closely mimicked the clinical and radiologic features of miliary tuberculosis. The overlapping characteristics posed significant diagnostic challenges, highlighting the need for a thorough differential diagnosis in similar presentations to ensure accurate and timely treatment.